Post-traumatic Stress Disorder in Karachites due to random events of violence - Ahmed , Sadaf; Noushad , Shamoon; Shahzad, Sehrish; Azher, Syed Zain; Aziz, Adnan; Saleem, Muhammad Taha (International Journal of Endorsing Health Science Research, 2014)
Karachi is one of the biggest City in Asia and since past 20 years terrorism in Karachi is increasing frequently, due to these terrorist activities people living here have developed several phobias and anxiety disorders. To contrast the occurrence of traumatic events and its relationship with symptoms of post-traumatic stress disorder in Karachites. Survey of residents of Karachi was conducted between January 12, 2011 and March 4, 2012. Symptoms of PTSD were assessed using questionnaire related to psycho social factors that prone to PTSD .Out of total 164 both male and females, 62% of respondents reported appetite changes due to these terrifying activities, 58% of respondents reported hostile personalities , depression & mood fluctuations, while remaining 30% reported insomnia. 76.82% reported depression According to their economical condition 71% Middle class was highly affected as compare to upper class and lower class. There was also a significant difference observed among the populations who are engaged both in education and also doing jobs for survivals. 88% of them were found frustrated & protesting against the situation of the city. The results of the current study suggest that the trauma incident by the resident population is significant. Stresses tend to be numerous and chronic. The trauma experienced correlated strongly with psycho social, somatic, PTSD symptoms and depression.